2018
DOI: 10.17221/260/2018-pse
|View full text |Cite
|
Sign up to set email alerts
|

No significant differences in rhizosphere bacterial communities between Bt maize cultivar IE09S034 and the near-isogenic non-Bt cultivar Zong31

Abstract: The release of genetically modified (GM) crops has potential to alter the bacterial population within rhizosphere. Here, the potential effect of GM maize cv. IE09S034 containing the Cry1Ie toxin gene from Bacillus thuringiensis (Bt) was investigated under the field conditions. The community composition and the relative abundance of the bacteria in rhizosphere soil were estimated by analysing 16S rRNA PCR amplicons. Our results indicated that Bt maize IE09S034 has no significant effects on the rhizosphere bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Some transgenic plants inhibit the growth of some microorganisms in the soil through root exudates, and promote the survival and reproduction of other microorganisms, resulting in favorable soil for plant growth ( Phour et al, 2020 ). Bt transgenic cotton ( G. hirsutum ), CrylAc + CpTI transgenic cotton and Cry1Ie transgenic maize ( Zea mays L.) showed that there were no significate differences for diversity and composition of rhizosphere soil microbial community with non-transgenic plant ( Zhang et al, 2015 ; Jingang et al, 2018 ; Li et al, 2018 ). In forestry, transgenic genetic poplar, such as insect resistant transgenic poplar, has been approved and become possibility of deployment ( Jing et al, 2004 ; Guifeng et al, 2006 ; Guifeng et al, 2006 ; Zhou et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some transgenic plants inhibit the growth of some microorganisms in the soil through root exudates, and promote the survival and reproduction of other microorganisms, resulting in favorable soil for plant growth ( Phour et al, 2020 ). Bt transgenic cotton ( G. hirsutum ), CrylAc + CpTI transgenic cotton and Cry1Ie transgenic maize ( Zea mays L.) showed that there were no significate differences for diversity and composition of rhizosphere soil microbial community with non-transgenic plant ( Zhang et al, 2015 ; Jingang et al, 2018 ; Li et al, 2018 ). In forestry, transgenic genetic poplar, such as insect resistant transgenic poplar, has been approved and become possibility of deployment ( Jing et al, 2004 ; Guifeng et al, 2006 ; Guifeng et al, 2006 ; Zhou et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The high-throughput sequencing results of Liang et al. showed that there were no significant differences in rhizosphere soil bacterial richness and diversity index and community structure between Cry1Ie transgenic maize and non-transgenic maize, while principal component analysis (PCA) showed that there were significant differences between seedling, flowering and maturity stages or between different test years ( Jingang et al., 2018 ). The bacterial species diversity and community structure in rhizosphere soil of Bt maize and non-Bt maize were studied by Illumina MiSeq sequencing technology ( van Wyk et al., 2017 ).…”
Section: High Throughput Sequencing Technologies Facilitating Soil Mi...mentioning
confidence: 99%
“…seedling, flowering and maturity stages or between test years (Jingang et al, 2018). The bacterial species diversity and community structure in rhizosphere soil of Bt maize and non-Bt maize were studied by Illumina MiSeq sequencing technology (van Wyk et al, 2017).…”
Section: A B D Cmentioning
confidence: 99%